2018
DOI: 10.15294/edaj.v7i3.22301
|View full text |Cite
|
Sign up to set email alerts
|

The Causality Variables of Financial Sector Deepening to Economic Growth in Indonesia 1986 - 2015

Abstract: This study aims to examine the causality and role as the variables of the financial sector deepening with economic growth in Indonesia. The test of causality in this research acres using heading Granger Causality Test and VECM test. The tests are conducted using annual data from 1986 to 2015. The result of research using heading Granger Causality shows that there is no causality between M2 ratio with economic growth. While the ratio of private credit by deposit money banks and gross fixed capital formation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…Finally, Salebu (2014) stated that the positive and significant effects of FDI on economic growth only exist in four sectors: crops and plantation, mining, the food industry, transportation, and communication. Financial progress calculated in the private credit ratio of deposit money banks has a uniform cause and economic growth in Indonesia (Astuti, 2018). Financial development at the regional level shows a positive and significant influence in Java (Baroroh, 2012) and (Supartoyo et al, 2018) found the same result for Sulawesi.…”
Section: Literature Reviewmentioning
confidence: 76%
“…Finally, Salebu (2014) stated that the positive and significant effects of FDI on economic growth only exist in four sectors: crops and plantation, mining, the food industry, transportation, and communication. Financial progress calculated in the private credit ratio of deposit money banks has a uniform cause and economic growth in Indonesia (Astuti, 2018). Financial development at the regional level shows a positive and significant influence in Java (Baroroh, 2012) and (Supartoyo et al, 2018) found the same result for Sulawesi.…”
Section: Literature Reviewmentioning
confidence: 76%
“…A research gap lies in the limited existing literature specifically analysing the influence of regional fiscal capacity on the convergence of inclusive economic development across the 34 provinces of Indonesia. While there have been studies on fiscal decentralisation and its impact on economic growth (Aprianti & Sulindrina, 2023;Baskaran & Feld, 2013;Canavire-Bacarreza et al, 2020;Jamil et al, 2022;Lamba et al, 2019), there is a necessity to further investigate the relationship between regional fiscal capacity and the convergence of inclusive economic development. This research analyses the influence of regional fiscal capacity on the convergence of inclusive economic development across 34 provinces in Indonesia.…”
Section: Introductionmentioning
confidence: 99%